Prompt closure versus gradual weaning of extraventricular drainage for hydrocephalus in adult patients with aneurysmal subarachnoid haemorrhage: a systematic review protocol with meta-analysis and trial sequential analysis. Issue 10 (1st October 2019) - Capion, Tenna; Lilja-Cyron, Alexander; Juhler, Marianne; Mathiesen, Tiit Illimar; Wetterslev, Jørn
Abstract : Introduction: In Neuro Intensive Care Units (NICU) and neurosurgical units, patients with an external ventricular drain (EVD) due to hydrocephalus following aneurysmal subarachnoid haemorrhage (SAH) are commonly seen. Cessation of the EVD involves the dilemma of either closing the EVD directly, or gradually weaning it before removal. Development of increased intracranial pressure (ICP) and acute hydrocephalus with subsequent need of a permanent shunt has been associated with prompt closure of theEVD, whereas increased risk of infection with possible spreading to the brain and subsequent patient fatality is suspected in connection to a longer treatment as seen in gradual weaning. Sparse data exist on the recommendation of cessation strategy and patients are currently being treated on the basis of personal experience and expert opinion. The objective of this systematic review is to assess the available evidence from clinical trials on the effects of prompt closure versus gradual weaning of EVD treatment for hydrocephalus in adult patients with SAH. Methods and analysis: We will search for randomised clinical trials in major international databases. Two authors will independently screen and select references for inclusion, extract data and assess the methodological quality of the included randomised clinical trials using the Cochrane risk of bias tool. Any disagreement will be resolved by consensus. We will analyse the extracted data using Review Manager and trial sequential analysis. To assess the quality of the evidence, we will create a 'Summary of Findings' table containing our primary and secondary outcomes using the GRADE assessment. Ethics and dissemination: Results will be published widely according to the interest of the society. No possible impact, harm or ethical concerns are expected doing this protocol. Trial registration number: PROSPERO CRD42018108801